(untitled) (Research, Society and Development, 2021)
Previous studies have shown that the clove essential oil concentration of 200 mg/kg did not present toxicity and histopathological changes in the liver. Based on the evidence presented in this study, we decided to evaluate in vivo the ability of a previously developed fermented dairy beverage, tested only in vitro, in which the standard chemical preservative, potassium sorbate, was replaced by clove essential oil (2 μl/ml), to be a functional food. To this end, twenty-four male Swiss mice were divided into three groups and submitted insulin sensitivity (IST) and glucose tolerance (GTT) testing, evaluation of physiological and biochemical parameters, histopathological analysis and quantification of the expression of anti-inflammatory and pro-inflammatory cytokines in the liver, after administering daily of the fermented dairy beverage with or without clove essential oil by gavage during 30 days. The group that received the fermented dairy beverage with clove essential oil showed a lower glycemic level in GTT, a higher sensitivity to insulin and a higher glucose decay constant rate (Kitt), with relation to the other groups. In the evaluation of physiological parameters there were no signs of toxicity in the mice during the experimental period. The biochemical parameters, histopathological analysis and expression of anti-inflammatory (IL-10) and pro-inflammatory (IL1β, IL6 e TNFα) cytokines in the liver of the mice, was not significantly affected by the treatment. These results corroborated by bioinformatics analysis demonstrate that the fermented dairy beverage with clove essential oil it can function as a substitute for conventional chemical preservatives and reduce glycemic levels.